Sharia Risk, The Indicator of Sharia Governance on Islamic Banks - Nur Alifah Fajariyah; Khusnul Khotimah (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2018)
Banking is a very vulnerable business to risk, so it takes good management to ensure itself as a healthy institutions. The governance of Islamic banking has a fundamental differences with the governance of conventional banking in terms of sharia compliance. The disobedience of the Islamic banking to the sharia compliance causes Islamic banks to be subject to sharia risk. The sharia risk is the possibility fot the operational of Islamic banks are not or will not be in compliance with established sharia principles and standards. Through a descriptive analysis by using library research, this study aims to map the flow of sharia risk in Islamic banks and categorizes its causes. This study notes the sharia risk arises from the purpose, politics, people, process, and systems. JEL Classification: G32, G34, O16